Transformational Leadership: A Pathway To Teacher’s Growth Mindset - Guavis, Ana Marie; Mala, Yuliana; Nettie, Nettie (JUPE : Jurnal Pendidikan Mandala, 2023)
Transformational leadership in a manner strategic can be applied to increase quality culture something school. Leadership style This oriented towards innovative and creative leadership as well as own attitude capable leadership motivating subordinates and the environment surrounding. Policy leadership transformational become reject measuring something agency for increase quality culture quality school because kindly definitively, leadership transformational is form values, beliefs, and needs that are capable bring change as form innovative. Objective study This are: analyzing the leadership model transformational to enhancement quality culture quality school. Study This use method study qualitative. Data collection using instrument study with disseminate questionnaire using google forms. Research results This are:(1) The study concluded that transformational leadership significantly contributes to cultivating a growth mindset among teachers, enhancing their professional development, and raising academic standards. Supportive leadership practices, collaborative learning platforms, and emphasis on educational qualifications were identified as effective strategies. (2) The findings also highlighted the importance of involving teachers in decision-making processes and addressing areas of improvement to further enhance teaching quality and student outcomes.